TECHNIQUES OF CCHP AS A RIGHT WAY TO APPLY THE 2ND LAW OF THERMODYNAMIC: CASE STUDY (PART ONE) - Patania, Francesco; Gagliano, Antonio; Nocera, Francesco; Antonio, Agrifoglio (European Scientific Journal, ESJ, 2015)
Paper illustrates the design of an â€œEfficient Energy Systemâ€ (EES) to supply energy to a new hospital of Catania (CH). It is shown the way to build EES through CCHP techniques and the analysis of energy request of EES during whole period of year. Paper shows also as EES , and connected CCHP techniques , achieves on the basis of 2nd Law of Thermodynamic significant economical decreasing of operational costs of CH and remarkable environmental benefits.